Performance of multigene testing in cytologically indeterminate thyroid nodules and molecular risk stratification - Yuanyuan Zhou; Xinping Wu; Yuzhi Zhang; Zhiqiang Li; Xia Ge; Hao Chen; Yuan Mao; Wenbo Ding (PeerJ, 2023)
Objective Thyroid cancer is the third most prevalent cancer among females. Genetic testing based on next-generation sequencing may provide an auxiliary diagnosis to reduce cytologically diagnostic uncertainty. However, commercial multigene tests are not widely available and are not well-tested in the Chinese population. Methods In this study, we designed a multigene testing panel and evaluated its performance in 529 cytologically indeterminate thyroid nodules (Bethesda III, IV and V). The molecular data of the DNA mutations and RNA fusions of fine needle aspiration samples were reviewed in conjunction with a clinical diagnosis, pathological reports, and definitive surgery for retrospective analysis. Then, the molecular risk stratification was investigated for its accuracy in malignant risk prediction. Results The overall combined consistency revealed substantial agreement (Kappa = 0.726) with the sensitivity, specificity, positive predictive value, and negative predictive values of 97.80%, 82.14%, 98.99%, and 67.65%, respectively. The most common aberration was BRAFV600E (82.59%), followed by NRAS mutants (4.07%), RET fusions (3.70%), and KRAS mutants (3.15%). Two cases (0.44%) were categorized into a high-risk group, 426 cases (94.67%) were categorized into a BRAF-like group with totally histopathologic papillary patterned tumors, and 22 cases (4.89%) were categorized into a RAS-like group with 14 papillary and eight follicular patterned tumors when the cohort concurrent aberrations were excluded. Potentially aggressive features may be related to concurrent molecular alterations of BRAFV600E with TERTQ302R, and AKT1L52R, NRASG12C, NRASQ61R, and CCDC6-RET fusions. Conclusions This study provided a multigene panel for identifying benign nodules from cytologically indeterminate thyroid nodules to avoid unnecessary surgery. We provide further evidence for using molecular risk stratification as a promising predictor of disease outcomes. The results of this study may be limited by the extremely high prevalence of cancer in the cohort for clinical reference.